Association between aspartate aminotransferase to alanine aminotransferase ratio and mortality in critically ill patients with end stage renal disease - Xiaomin Liang; Qian Wang; Kai Lai; Xiaohong Li; Shuiqing Gui; Ying Li; Zemao Xing (Scientific Reports)
Abstract The aspartate aminotransferase to alanine aminotransferase (AST/ALT) ratio has been extensively studied in relation to mortality, yet its specific association with intensive care unit (ICU) mortality in end stage renal disease (ESRD) patients remains underexplored. The study investigated this relationship in critically ill ESRD patients. This multicenter retrospective cohort study analyzed data from ESRD patients admitted to 208 ICUs across the United States between 2014 and 2015 using the eICU Collaborative Research Database. Smooth curve fitting with Generalized Additive Model and two-piecewise linear regression analyses were utilized to examine nonlinear relationships. Among the 3005 patients (mean age 62.68 ± 14.16 years; 54.48% male), 252 (8.39%) died in the ICU. A significant nonlinear relationship between the AST/ALT ratio and ICU mortality was identified with an inflection point of 1.59. For AST/ALT ratios ≤ 1.59, each unit increase was associated with a 2.02-fold higher risk of ICU mortality (OR 2.02, 95% CI 1.22–3.33, P = 0.0059). For AST/ALT ratios > 1.59, no significant association with mortality was observed (OR  1.07, 95% CI 0.86–1.33, P = 0.5348). Sensitivity analyses confirmed the robustness of these findings. In critically ill ESRD patients, a nonlinear relationship exists between AST/ALT ratio and ICU mortality.